PENERAPAN PASAL MENGUNTUNGKAN TERPIDANA - Marpaung, Aldi Yosep; Haryanto, Muh (The Juris, 2024)
This article discusses the benefits for convicts in the context of changes to statutory regulations which state that the convict’s actions are no longer a criminal. As stated in Article 3 paragraph (4) of the new Criminal Code. So, how can the material law like Article 3 paragraph (4) of the new Criminal Code be implemented? Based on normative research through qualitative methods and normative juridical approaches, the author will answer this question through several considerations of mechanisms as an effort taken by convicts through judicial review, cassation for legal purposes, clemency, and amnesty. Judicial review, cassation for legal purposes, and clemency will be considered as petition efforts from convicts regarding the implementation of Article 3 paragraph (4) of the new Criminal Code. Meanwhile, amnesty will be considered as an effort from the community or the government’s intention in implementing Article 3 paragraph (4) of the new Penal Code.